Surface roughness effect on copper–alumina adhesion - Lim, Ju Dy (2016)
The surface roughness of the substrate itself could play an important role for the bonding at the interface. In this paper, a correlation of the surface roughness of a rigid alumina substrate and its 2D model of estimated surface area has been studied using Atomic Force Microscopy (AFM). With rougher surface, the adhesive strength between a deposited copper film and the alumina substrate is higher due to the larger contact area at the interface. For 99.99% pure copper–96% pure alumina, this effect can account for an adhesive strength increment of more than 50%.